ABHRAK BHASMA AND SiO2 INFLUENCED FREE RADICAL STATUS IN LIVER AND KIDNEY OF CCl4-INDUCED ACUTELY INTOXICATED MALE ALBINO RAT - B TELI, PARASHURAM; A KANASE, ARUNA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to study the mechanism of action of abhrak bhasma-mediated liver and kidney protection in CCl4-induced acute hepatotoxicity-induced male albino rats. Action of abhrak bhasma is compared with the action of SiO2 in similar experimental conditions to differentiate the role of silicon. Methods: Male albino rats (Rattus norvegicus) were used for experiments. The acute hepatotoxicity was induced by daily dose of CCl4 (3.0 ml/kg body wt for 7 days consecutive). Concurrent treatment of abhrak bhasma in graded doses (10, 20, 30, and 40 mg) was given for 7 days (PO). SiO2 (10, 20, 30, and 40 mg) in graded doses was also given in independent groups of rats as silica control. Lipid peroxidation (LPO) in liver and kidney was studied by malondialdehyde (MDA) estimations as parameter of toxicity and also to study protection. Results: CCl4-induced hepatotoxicity (MDA levels) is partially managed by low doses of SiO2 but not by high doses. Abhrak bhasma hepatoprotective activities were dose dependent. A 40 mg dose maintained normal levels of LPO. Abhrak bhasma also protected associated renal toxicity. Conclusion: Abhrak bhasma protected CCl4-induced hepatotoxicity and also associated renal toxicity. Silicon from both SiO2 and abhrak bhasma is hepatoprotective in 10 ml doses (10 and 20 mg) but silicon processed in abhrak bhasma by traditional Ayurvedic processes increased its potency and hepatoprotection and added the potency of renal protection.